2018
DOI: 10.1111/cmi.12859
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide mRNA-miRNA profiling uncovers a role of the microRNA miR-29b-1-5p/PHLPP1 signalling pathway inHelicobacter pylori-driven matrix metalloproteinase production in gastric epithelial cells

Abstract: Aberrant expression of microRNAs (miRNAs) is associated with tumour progression, extracellular matrix remodelling, and cell proliferation. miRNAs modulate host gene expression during infection by pathogens such as Helicobacter pylori, which is associated with varying degrees of gastric pathology. In order to gain insight into the regulation of gene expression by miRNAs during H. pylori infection of gastric epithelial cells and its likely downstream consequences, we analysed the transcriptomes and miRnomes of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…Gastric carcinogenesis requires genomic instabilities; however, the mechanisms of H. pylori induction of genomic instabilities remains poorly understood (Hanada et al , 2014; Koeppel et al , 2015). In this study, we extend these observations by showing that H. pylori induced an increase in the intracellular ROS levels, DNA DSBs, and DNA SSBs in the gastric cancer cell line AGS, which has been routinely used in cell culture system infected by H. pylori in vitro (Wang et al , 2016; Datta et al , 2018). To comprehensively explore the occurrence of DNA damage in the H. pylori -infected cells, we measured ROS levels, DNA damage, cell cycle checkpoint activation, and subsequent cell growth.…”
Section: Discussionsupporting
confidence: 70%
“…Gastric carcinogenesis requires genomic instabilities; however, the mechanisms of H. pylori induction of genomic instabilities remains poorly understood (Hanada et al , 2014; Koeppel et al , 2015). In this study, we extend these observations by showing that H. pylori induced an increase in the intracellular ROS levels, DNA DSBs, and DNA SSBs in the gastric cancer cell line AGS, which has been routinely used in cell culture system infected by H. pylori in vitro (Wang et al , 2016; Datta et al , 2018). To comprehensively explore the occurrence of DNA damage in the H. pylori -infected cells, we measured ROS levels, DNA damage, cell cycle checkpoint activation, and subsequent cell growth.…”
Section: Discussionsupporting
confidence: 70%
“…35 Downregulation of miR-92a is associated with aggressive breast cancer features. 36 Specifically, among these identified miR-NAs, miR-29b-1-5p could upregulate Akt-dependent nuclear factor kappa B (NF-κB) signaling leading to activation of MMP2 and MMP9, 37 which had been found to play key roles in VM formation of HCC in our previous study. 1,2 Collectively, our study suggested that the miRNAs regulated by n339260 were cancerrelated miRNAs that might be involved in HCC aggressiveness.…”
Section: Discussionmentioning
confidence: 91%
“…PHLPP1 has been reported to be a target of miR-29b-1-5p 30 . Therefore, we investigated the role of PHLPP1 in Da0324-induced growth inhibition of GC cells.…”
Section: Resultsmentioning
confidence: 99%
“…PHLPP1 has been reported to be a direct target of miR-29b-1-5p 30 . Knockdown of miR-29b-1-5p inhibited the migration of AGS cells, knockdown of PHLPP1 increased migration rates in Helicobacter pylori-treated AGS cells 30 .…”
Section: Discussionmentioning
confidence: 99%